2019
DOI: 10.1007/s10787-019-00626-0
|View full text |Cite
|
Sign up to set email alerts
|

Jasonia glutinosa (L.) DC., a traditional herbal medicine, reduces inflammation, oxidative stress and protects the intestinal barrier in a murine model of colitis

Abstract: Jasonia glutinosa (L.) DC., known as rock tea (RT), is traditionally used in Spain as a digestive due to its beneficial properties in bowel disorders. The pharmacological nature of these properties has not been established yet. The aim of this work was to evaluate the therapeutic utility of RT in experimental colitis and to identify chemical constituents with anti-inflammatory and/or anti-oxidative properties. RT extract was prepared with ethanol in a Soxhlet apparatus and analysed by HPLC-DAD. Superoxide radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…Ethnobotanical studies on this plant report that its main use, as an infusion, is for the treatment of diarrhea, dyspepsia or abdominal pain [ 2 ]. These digestive properties were demonstrated for the first time in a murine model of colitis [ 3 , 4 ]. In these studies, the oral administration of an ethanolic extract of RT (5, 25 and 50 mg/kg) ameliorated colitis symptomatology, prevented the macroscopic damage and histological changes induced by dextran sulfate sodium in mice and normalized the intestinal contractibility and the intestinal total transit disrupted by the colitis [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ethnobotanical studies on this plant report that its main use, as an infusion, is for the treatment of diarrhea, dyspepsia or abdominal pain [ 2 ]. These digestive properties were demonstrated for the first time in a murine model of colitis [ 3 , 4 ]. In these studies, the oral administration of an ethanolic extract of RT (5, 25 and 50 mg/kg) ameliorated colitis symptomatology, prevented the macroscopic damage and histological changes induced by dextran sulfate sodium in mice and normalized the intestinal contractibility and the intestinal total transit disrupted by the colitis [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these effects could be explained by anti-inflammatory [ 4 , 8 ] or antioxidant effects [ 4 , 5 , 9 ], which are related to its phytochemical composition. A recent in vivo study has shown that dietary supplementation with RT (10 or 30%) for 15 or 30 days in sea bream ( Sparus aurata L. ) improves short-term immunostimulatory capacity (15 days) and maintains antioxidant capacity in the long-term (30 days) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the large amounts of NO• generated from iNOS have been implicated in tissue damage and intestinal inflammation [ 52 ]. On the other hand, evidence from experimental models of intestinal inflammation demonstrate an up-regulation of iNOS expression [ 10 , 53 ]. In the present research, we observed a significative decrease in the expression of iNOS protein in the Preventive and Curative treatment groups with Ach.…”
Section: Discussionmentioning
confidence: 99%